The Sindh Education Sector Reform Project(SESRP) on educational quality in Primary schools within the Hyderabad Region Pakistan - Mallah, Imtiaz Ali; Khoso, Imam Uddin; Nawaz, Muhammad (Pakistan Business Review, 2023)
The Sindh Education Sector Reform Project (SESRP) was a Sindh government project in Pakistan that refers to expand the quality of education in primary schools within the Hyderabad region. For the first time, the Sindh government has taken steps to assess how school leadership affects basic education quality. They also intend to examine all other aspects that affect primary school education quality and suggest appropriate steps to improve primary education quality. This study aims to investigate and expand our basic knowledge of (SESRP), leadership, and educational quality. by adding to the body of knowledge During the collection of a representative sample, the researchers used purposeful and judgmental sampling approaches. The study used thematic analysis to analyse material that was passed from one person to another. Content analysis and documentary analysis were used to conduct face-to-face interviews. The findings revealed that school leaders (headmasters) have worked extremely hard to provide quality education in primary schools throughout the Hyderabad Region, despite numerous challenges. If this project is not fully implemented, education will suffer, and the efforts of Headmasters will be wasted. On top of the domino effect, the recommendation is based on a literature review.